Assessment of Andisol characteristics for the development of potato crops in Pangalengan - Herdiansyah, Ganjar; Arifin, Mahfud; Suriadikusumah, Abraham; Herawati, Aktavia (JOURNAL OF TROPICAL SOILS, 2025)
Pangalengan is a horticultural crop center area in Bandung Regency. The soil in this area consist of Andisol, which is developed from volcanic ash. One of the primary commodities in this area is potatoes. Intensive farming in Pangalengan is a problem that has an impact on soil and environmental conditions, thereby disrupting crop productivity. The research aimed to assess the characteristics of Andisols for the development of potato crop in Pangalengan. This research used qualitative, descriptive, and survey methods. The survey based on physiographic methods. Soil samples were taken purposively. The observations consisted of soil characteristics, erosion, soil fertility and land suitability. The research results show that the soil type is Typic Hapludans. Erosion is moderate (19.06-94.41 tons/ha/year) in SMU 1 and 2, high (311.22 tons/ha/year) in SMU 3 and very high (798.04 tons/ha/year) in SMU 4, soil fertility is low with land suitability for potato crop including marginally suitable (S3) and not suitable (N). Fertilization, especially P fertilizer and organic fertilizer as well as making bunds in the direction of the contour, are recommended for the development of potato crops in Pangalengan.